Analysis of Legal Protection for Consumers in Trading Through Electronic Systems Based on Minister of Trade Regulation Number 31 of 2023 - I Made Rai Buda Tantra Yoga Suarsawan; I Nyoman Prabu Buana Rumiartha; Ni Putu Adhya Pradnyaswari (Focus Journal : Law Review, 2024)
Trading Through Electronic Systems (PMSE) is a type of trading that is different from conventional trading because it uses an electronic systems. With the rapid advancement of technology, PMSE continues to grow with the emergence of various types of electronic trading. The purpose of this research is to analyze the types of trading through electronic systems and the legal protection provided to consumers engaging in PMSE based on Minister of Trade Regulation Number 31 of 2023. The method used in this research is normative legal research. Normative research involves a literature review with a statutory approach. The results of this study identify various types of PMSE according to Minister of Trade Regulation Number 31 of 2023, as well as several forms of legal protection for consumers participating in PMSE. However, the legal protection offered under this regulation still refers to the Consumer Protection Act. This aspect requires updating, considering the diverse types and forms of PMSE that have emerged.